Antimicrobial resistance in biofilms: Exploring marine actinobacteria as a potential source of antibiotics and biofilm inhibitors - Nikky Goel; Syeda Warisul Fatima; Sumit Kumar; Rajeshwari Sinha; Sunil K. Khare (Biotechnology Reports, 2021)
Antimicrobial resistance (AMR) is one of the serious global public health threats that require immediate action. With the emergence of new resistance mechanisms in infection-causing microorganisms such as bacteria, fungi, and viruses, AMR threatens the effective prevention and treatment of diseases caused by them. This has resulted in prolonged illness, disability, and death. It has been predicted that AMR will lead to over ten million deaths by 2050. The rapid spread of multidrug-resistant bacteria is also causing old antibiotics to become ineffective. Among the diverse factors contributing to AMR, intrinsic biofilm development has been highlighted as an essential contributing facet. Moreover, biofilm-derived antibiotic tolerance leads to serious recurrent chronic infections. Therefore, the discovery of novel bioactive molecules is a potential solution that can help combat AMR. To achieve this, sustained mining of novel antimicrobial leads from actinobacteria, particularly marine actinobacteria, can be a promising strategy. Given their vast diversity and different habitats, the extraordinary capacity of actinobacteria can be tapped to synthesize new antibiotics or bioactive molecules for biofilm inhibition. Advanced screening strategies and novel approaches in the field of modern biochemical and molecular biology can be used to detect such new compounds. In view of this, the present review focuses on understanding some of the recent strategies to inhibit biofilm formation and explores the potential role of marine actinobacteria as sources of novel antibiotics and biofilm inhibitor molecules.